2020
DOI: 10.1053/j.gastro.2020.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Aspirin Reduces Colorectal Tumor Development in Mice and Gut Microbes Reduce its Bioavailability and Chemopreventive Effects

Abstract: Author names in bold designate shared co-first authorship.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
65
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(75 citation statements)
references
References 44 publications
3
65
0
Order By: Relevance
“…2 In line with our study, a recent animal study demonstrated that stool samples from mice fed with aspirin had an increase in anti-inflammatory bacteria and reduction in pro-inflammatory bacteria. 3 Also consistent with our findings, a recent cross-sectional study did not detect a difference in microbiome diversity, but did find a difference in individual taxa in 20 individuals who did and did not receive combined anti-platelet treatment including aspirin and clopidogrel. 4 We agree that some observed changes in our study might be explained by diet or use of drugs, other than aspirin, due to the differential changes in aspirin and placebo arms during intervention.…”
Section: N V I T E D E D I T O R I a L Editorial: The Microbiome Asupporting
confidence: 92%
See 1 more Smart Citation
“…2 In line with our study, a recent animal study demonstrated that stool samples from mice fed with aspirin had an increase in anti-inflammatory bacteria and reduction in pro-inflammatory bacteria. 3 Also consistent with our findings, a recent cross-sectional study did not detect a difference in microbiome diversity, but did find a difference in individual taxa in 20 individuals who did and did not receive combined anti-platelet treatment including aspirin and clopidogrel. 4 We agree that some observed changes in our study might be explained by diet or use of drugs, other than aspirin, due to the differential changes in aspirin and placebo arms during intervention.…”
Section: N V I T E D E D I T O R I a L Editorial: The Microbiome Asupporting
confidence: 92%
“…9 Furthermore, when designing future trials, researchers should account for the latest findings from animal and human studies, because this field is developing rapidly. For instance, Zhao et al 3 not only showed that aspirin affects gut microbiome, but also found that certain bacteria--Lysinibacillus sphaericus--degrade aspirin and impair its anti-cancer effect. That finding implies that aspirin would not be useful among those with a higher abundance of Lysinibacillus sphaericus.…”
Section: N V I T E D E D I T O R I a L Editorial: The Microbiome Amentioning
confidence: 99%
“…Other studies have shown complex interactions between aspirin and gut flora. 2,3 We are particularly interested in the possible use of microbiota-based interventions to improve aspirin use for CRC prevention.…”
Section: Letter: Synergistic Role Of Gut Flora With Aspirin To Prevenmentioning
confidence: 99%
“…Furthermore, aspirin resistance might also hinder the expanded clinical use of aspirin in the population, which could be caused by abundance of some aerobic gut microbes degrading aspirin and decreasing its plasma levels. 3 Gut flora modulation could be synergistic with aspirin in reducing CRC risk as follows: probiotics could be used to reduce the risk of small intestinal enteropathy caused by aspirin, 5 and use of specific probiotics, prebiotics or faecal microbiota transplantation could alleviate or reverse aspirin resistance by targeted modulations. 3,6 Finally, re-setting the inflammatory microenvironment by inhibiting the formation of trimethylamine N-oxide, a gut microbial metabolite and CRC risk factor, 7,8 could delay or stop the adenoma-cancer progression.…”
Section: Letter: Synergistic Role Of Gut Flora With Aspirin To Prevenmentioning
confidence: 99%
“…On one hand, the gut microorganisms attenuated the preventive effect of aspirin by biotransformation of aspirin into its inactive metabolites, and on the other hand, aspirin enriched the abundance of some probiotics in the gut microbiota, which in turn provided some protections against CRC development (Figure 1). Although the deactivation of aspirin by the gut microbiota, which can compromise the antithrombotic effect of aspirin, has already been previously reported [11], the study by Zhao et al [10] is novel for identifying the bacterial species responsible for deactivating aspirin and potentially affecting aspirin CRC chemoprevention efficacy. The findings in this study have potential clinical relevance.…”
mentioning
confidence: 99%